Técnica de deslizamiento neural en síndrome de piriforme en el adulto - Erazo Barona, Lissette Katherine (2022)
ABSTRACT The present investigation entitled neural sliding technique in piriformis syndrome belonging to the line of health research in physical rehabilitation aims to determine the effectiveness of the neural sliding technique as part of the rehabilitation in patients with piriformis syndrome, through the compilation and analysis of scientific articles, to reinforce knowledge and improve reading comprehension. The scientific research consisted of the search for scientific articles, collecting a total of 85 scientific articles from 2012 to 2022; After being analyzed and qualified with a score equal to or greater than 6 points on the Pedro methodological scale, 35 articles were finally selected that met the inclusion and exclusion criteria. The articles were found in different databases, including PubMed, Scielo, Elsevier and Scopus; in languages such as English, Portuguese and Spanish; Its efficacy has been corroborated with the interpretation of the results presented in clinical trials, demonstrating that the application of the neural sliding technique in patients with piriformis syndrome improves pain, increases the range of movement and decreases the degree of disability caused by piriformis syndrome. pathology Keywords: Neurodynamics, neural sliding, piriformis syndrome, sciatic nerve.